Costa Rica, from special education to inclusive education. A historical perspective - Deliyore Vega, María del Rocío (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
Special education in Latin America is at a time of constant transformation due to the evolution of the concept of disability and the emergence of the new paradigm of inclusive education. The objective of this article is to recapitulate this transformation. We focus on the Costa Rican changes in this discipline and analyze the challenges that still prevail. For this, a historical documentary research centered on the verification and validation of sources was carried out. After analyzing the conceptual evolution of disability and special education in Costa Rica and Latin America, it is concluded that segregationist services prevail while inclusive education services emerge. This implies the need for an epistemological analysis of special education in Costa Rica that shapes the new perspectives of the discipline and promotes forceful changes in order to protect the human rights of people with disabilities.